2022
DOI: 10.1200/jco.21.00838
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib Plus Rituximab Versus Placebo Plus Rituximab for Waldenström's Macroglobulinemia: Final Analysis From the Randomized Phase III iNNOVATE Study

Abstract: PURPOSE The double-blind, randomized, placebo-controlled phase III iNNOVATE study showed sustained efficacy of ibrutinib-rituximab in Waldenström's macroglobulinemia (WM). Here, we present the final analysis from iNNOVATE. METHODS Patients had confirmed symptomatic WM, either previously untreated or previously treated; patients with prior rituximab had at least a minor response to their last rituximab-based regimen. Patients were randomly assigned to once-daily ibrutinib 420 mg plus rituximab or placebo plus r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 19 publications
9
79
1
Order By: Relevance
“…21 Upon a relatively longer follow-up of 60 months, similar patterns of response for ibrutinib and rituximab in both TN and R/R patients were reported. 16 When considering the mutational status, we found superior MRR and VGPR rates with MYD88 mutated + CXCR4 wild-type patients in 1st-generation BTKi, this effect was also observed in the total cohort of both 1st-and 2nd-generation BTKi. This may be explained by the resulting disturbances of multiple prosurvival cascades including the NF-KB, AKT, ERK, and STAT3 activation when mutated MYD88 is targeted.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…21 Upon a relatively longer follow-up of 60 months, similar patterns of response for ibrutinib and rituximab in both TN and R/R patients were reported. 16 When considering the mutational status, we found superior MRR and VGPR rates with MYD88 mutated + CXCR4 wild-type patients in 1st-generation BTKi, this effect was also observed in the total cohort of both 1st-and 2nd-generation BTKi. This may be explained by the resulting disturbances of multiple prosurvival cascades including the NF-KB, AKT, ERK, and STAT3 activation when mutated MYD88 is targeted.…”
Section: Discussionsupporting
confidence: 52%
“…First-generation BTKi had a 60-month OS ranging from 73% to 87% in included studies with a median of 50 months (95% CI, 11-not reached) reported in one study. [16][17][18]21 For 60 months PFS, rates ranged from 40% to 54% with a median of 39 months (95% CI, 25-not reached). 17 As for 2ndgeneration BTKi, the longest OS was reported on the 36-month mark in two studies, 84.8% and 76.2%.…”
Section: Resultsmentioning
confidence: 99%
“…However, this study does not answer the question whether rituximab adds value to ibrutinib alone since it lacks an ibrutinib monotherapy arm. The updated long-term data of these pivotal studies of ibrutinib in the relapse and front-line setting and of the iNNOVATE trial have been recently published, further confirming the efficacy and safety profiles (56)(57)(58).…”
Section: Btk Inhibitorsmentioning
confidence: 69%
“…29 The 4-year PFS rate in the treatment-naïve cohort was 70% and 32% respectively and in those previously treated, 71% and 20%. 80 A subsidiary study of this trial investigated the role of ibrutinib alone in 31 patients with rituximab-refractory disease. After a median follow-up of 58 months, the median PFS was 39 months (95% CI 25-not evaluable).…”
Section: Btk Inhibitorsmentioning
confidence: 99%